2023
DOI: 10.1108/jhass-09-2023-0111
|View full text |Cite
|
Sign up to set email alerts
|

Political change, elections, and stock market indicators: a generalized method of moment analysis

Eric B. Yiadom,
Valentine Tay,
Courage E.K. Sefe
et al.

Abstract: PurposeThe performance of financial markets is significantly influenced by the political environment during general elections. This study investigates the effect of general elections on stock market performance in selected African markets.Design/methodology/approachPrior studies have been inconsistent in determining whether electioneering events negatively or positively influence stock market performance. The study utilized panel data set with annual observations from 1990 to 2020. The generalized method of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The interest rate is an indicator in determining whether someone will invest or save. Yiadom et al (2024), with research on election events that influence capital market performance, found that election activities had a positive impact on capital market performance, while changes in government had a negative impact. As a result, the study recommends that stock market stakeholders remain vigilant and actively monitor election events to design and implement effective policies aimed at reducing political risks during general elections.…”
Section: ) Interest Ratementioning
confidence: 99%
“…The interest rate is an indicator in determining whether someone will invest or save. Yiadom et al (2024), with research on election events that influence capital market performance, found that election activities had a positive impact on capital market performance, while changes in government had a negative impact. As a result, the study recommends that stock market stakeholders remain vigilant and actively monitor election events to design and implement effective policies aimed at reducing political risks during general elections.…”
Section: ) Interest Ratementioning
confidence: 99%